Astrocytes phenomics as new druggable targets in healthy aging and Alzheimer’s disease progression - Lana, Daniele; Ugolini, Filippo; Iovino, Ludovica; Attorre, Selene; Giovannini, Maria Grazia (Frontiers in Cellular Neuroscience, 2025)
For over a century after their discovery astrocytes were regarded merely as cells located among other brain cells to hold and give support to neurons. Astrocytes activation, “astrocytosis” or A1 functional state, was considered a detrimental mechanism against neuronal survival. Recently, the scientific view on astrocytes has changed. Accumulating evidence indicate that astrocytes are not homogeneous, but rather encompass heterogeneous subpopulations of cells that differ from each other in terms of transcriptomics, molecular signature, function and response in physiological and pathological conditions. In this review, we report and discuss the recent literature on the phenomic differences of astrocytes in health and their modifications in disease conditions, focusing mainly on the hippocampus, a region involved in learning and memory encoding, in the age-related memory impairments, and in Alzheimer’s disease (AD) dementia. The morphological and functional heterogeneity of astrocytes in different brain regions may be related to their different housekeeping functions. Astrocytes that express diverse transcriptomics and phenomics are present in strictly correlated brain regions and they are likely responsible for interactions essential for the formation of the specialized neural circuits that drive complex behaviors. In the contiguous and interconnected hippocampal areas CA1 and CA3, astrocytes show different, finely regulated, and region-specific heterogeneity. Heterogeneous astrocytes have specific activities in the healthy brain, and respond differently to physiological or pathological stimuli, such as inflammaging present in normal brain aging or beta-amyloid-dependent neuroinflammation typical of AD. To become reactive, astrocytes undergo transcriptional, functional, and morphological changes that transform them into cells with different properties and functions. Alterations of astrocytes affect the neurovascular unit, the blood–brain barrier and reverberate to other brain cell populations, favoring or dysregulating their activities. It will be of great interest to understand whether the differential phenomics of astrocytes in health and disease can explain the diverse vulnerability of the hippocampal areas to aging or to different damaging insults, in order to find new astrocyte-targeted therapies that might prevent or treat neurodegenerative disorders.